The green profiles : using social media for communicating corporate environmental issues to external stakeholders - Bui, Nghiem Dac Vinh (2018)
Sustainability is an essential part of doing business nowadays. Corporate sustainability communication (CSC) assists companies to conduct dialogues with stakeholders regarding sustainability topics. In addition, social media has emerged as both challenge and opportunity for CSC. This paper studied the situation of using social media platforms for communicating corporate environmental issues with external stakeholders at four Nordic aviation companies: Scandinavian Airlines (SAS), Finnair, Icelandair, and Norwegian Air Shuttle.